Experimental Autoimmune Encephalomyelitis Induction in Genetically B Cell–deficient Mice - Wolf, Susan D. (The Rockefeller University Press, 1996)
Experimental autoimmune encephalomyelitis (EAE) is an animal model for autoimmune central nervous system disease mediated by CD4 T cells. To examine the role of B cells in the induction of EAE, we used B10.PL (I-A(u)) mice rendered deficient in B cells by deletion of their μ chain transmembrane region (B10.PLμMT). By immunizing B10.PL and B10.PLμMT mice with the NH-terminal myelin basic protein encephalitogenic peptide Ac1-11, we observed no difference in the onset or severity of disease in the absence of mature B cells. There was, however, a greater variation in disease onset, severity, and especially of recovery in the B cell–deficient mice compared to controls. B10.PLμMT mice rarely returned to normal in the absence of B cells. Taken together, our data suggest that B cells do not play a role in the activation of encephalitogenic T cells, but may contribute to the immune modulation of acute EAE. The mechanisms to explain these effects are discussed.